Dynamic response characteristics of dry and water-saturated schist under impact loading - Yang Zhou; Sheng-rui Su; Jian-xun Chen (Journal of Mountain Science, 2020)

Spatial and Temporal Distributions of Atmospheric CO2 in East China Based on Data from Three Satellites - Bozhen Li; Gen Zhang; Lingjun Xia; Ping Kong; Mingjin Zhan; Rui Su (Advances in Atmospheric Sciences, 2020)

Os4BGlu14, a monolignol β-Glucosidase, negatively affects seed longevity by influencing primary metabolism in rice - Rui-Juan Ren; Pei Wang; Li-Na Wang; Jing-Ping Su; Lin-Jing Sun; Yue Sun; De-Fu Chen; Xi-Wen Chen (Plant Molecular Biology, 2020)

Sharing of Genetic Association Signals by Age-Related Macular Degeneration and Alzheimer’s Disease at Multiple Levels - Handan Tan; Meng Lv; Xiao Tan; Guannan Su; Rui Chang; Peizeng Yang (Molecular Neurobiology, 2020)

Multi-AUVs Cooperative Target Search Based on Autonomous Cooperative Search Learning Algorithm - Yuan Liu; Min Wang; Zhou Su; Jun Luo; Shaorong Xie; Yan Peng; Huayan Pu; Jiajia Xie; Rui Zhou (Journal of Marine Science and Engineering, 2020)
As a new type of marine unmanned intelligent equipment, autonomous underwater vehicle (AUV) has been widely used in the field of ocean observation, maritime rescue, mine countermeasures, intelligence reconnaissance, etc. Especially in the underwater search mission, the technical advantages of AUV are particularly obvious. However, limited operational capability and sophisticated mission environments are also difficulties faced by AUV. To make better use of AUV in the search mission, we establish the DMACSS (distributed multi-AUVs collaborative search system) and propose the ACSLA (autonomous collaborative search learning algorithm) integrated into the DMACSS. Compared with the previous system, DMACSS adopts a distributed control structure to improve the system robustness and combines an information fusion mechanism and a time stamp mechanism, making each AUV in the system able to exchange and fuse information during the mission. ACSLA is an adaptive learning algorithm trained by the RL (Reinforcement learning) method with a tailored design of state information, reward function, and training framework, which can give the system optimal search path in real-time according to the environment. We test DMACSS and ACSLA in the simulation test. The test results demonstrate that the DMACSS runs stably, the search accuracy and efficiency of ACSLA outperform other search methods, thus better realizing the cooperation between AUVs, making the DMACSS find the target more accurately and faster.

Hydrogeochemical and isotopic characteristics of groundwater in Xinchang preselected site and their implications - Zhichao Zhou; Ju Wang; Rui Su; Yonghai Guo; Jingbo Zhao; Ming Zhang; Ruili Ji; Yanan Li; Jiebiao Li (Environmental Science and Pollution Research, 2020)

Erratum to: Transmission risk of patients with COVID-19 meeting discharge criteria should be interpreted with caution - Jun-wei Su; Wen-rui Wu; Guan-jing Lang; Hong Zhao; Ji-fang Sheng (Journal of Zhejiang University-SCIENCE B, 2020)

Prefrontal Nectin3 Reduction Mediates Adolescent Stress-Induced Deficits of Social Memory, Spatial Working Memory, and Dendritic Structure in Mice - Hong-Li Wang; Ji-Tao Li; Han Wang; Ya-Xin Sun; Rui Liu; Xiao-Dong Wang; Yun-Ai Su; Tian-Mei Si (Neuroscience Bulletin, 2020)
Chronic stress may disrupt the normal neurodevelopmental trajectory of the adolescent brain (especially the prefrontal cortex) and contribute to the pathophysiology of stress-related mental illnesses, but the underlying molecular mechanisms remain unclear. Here, we investigated how synaptic cell adhesion molecules (e.g., nectin3) are involved in the effects of adolescent chronic stress on mouse medial prefrontal cortex (mPFC). Male C57BL/6N mice were subjected to chronic social instability stress from postnatal days 29 to 77. One week later, the mice exposed to chronic stress exhibited impaired social recognition and spatial working memory, simplified dendritic structure, and reduced spine density in the mPFC. Membrane localization of nectin3 was also altered, and was significantly correlated with behavioral performance. Furthermore, knocking down mPFC nectin3 expression by adeno-associated virus in adolescent mice reproduced the stress-induced changes in behavior and mPFC morphology. These results support the hypothesis that nectin3 is a potential mediator of the effects of adolescent chronic stress on prefrontal structural and functional abnormalities.

Neurofeedback Training for Brain Functional Connectivity Improvement in Mild Cognitive Impairment - Xin Li; Jie Zhang; Xiang-Dong Li; Wei Cui; Rui Su (Journal of Medical and Biological Engineering, 2020)

Dissecting the Potential of Selenoproteins Extracted from Selenium-Enriched Rice on Physiological, Biochemical and Anti-Ageing Effects In Vivo - Rui Zeng; Muhammad Umer Farooq; Guo Zhang; Zhichen Tang; Tengda Zheng; Yang Su; Sajad Hussain; Yuanke Liang; Xiaoying Ye; Xiaomei Jia; Jianqing Zhu (Biological Trace Element Research, 2020)

Clinical strategies for differentiating IgG4-related cholecystitis from gallbladder carcinoma to avoid unnecessary surgical resection - Rui Zhang; Hao-Ming Lin; Zhao-Xi Cai; Su-Juan Du; Hong Zeng; Lei-Bo Xu; Jie Wang; Chao Liu (Science China Life Sciences, 2020)

Transmission risk of patients with COVID-19 meeting discharge criteria should be interpreted with caution - Jun-wei Su; Wen-rui Wu; Guan-jing Lang; Hong Zhao; Ji-fang Sheng (Journal of Zhejiang University-SCIENCE B, 2020)

Impact of selenium, zinc and their interaction on key enzymes, grain yield, selenium, zinc concentrations, and seedling vigor of biofortified rice - Hla Hla Ei; Tengda Zheng; Muhammad Umer Farooq; Rui Zeng; Yang Su; Yujie Zhang; Yuanke Liang; Zhichen Tang; Xiaoying Ye; Xiaomei Jia; Jianqing Zhu (Environmental Science and Pollution Research, 2020)

Characteristics and dynamics of the Ganqiuchi rock avalanche triggered by a paleo-earthquake in the Northern Qinling Mountains - Ze-Hua Zhou; Yan Lyu; Sheng-rui Su; Shi-jie Liu; Hui Zhao; Peng Li; Yang Zhou (Journal of Mountain Science, 2020)

Release of tartrate as a major carboxylate by alfalfa (Medicago sativa L.) under phosphorus deficiency and the effect of soil nitrogen supply - Honghua He; Miaomiao Wu; Lei Guo; Chenbin Fan; Zekun Zhang; Rui Su; Qi Peng; Jiayin Pang; Hans Lambers (Plant and Soil, 2020)

Tracing solute sources and carbon dynamics under various hydrological conditions in a karst river in southwestern China - Jing Liu; Bo Chen; Zhu-Yan Xu; Yuan Wei; Zhi-Hua Su; Rui Yang; Yong-Xue Ji; Xiao-Dan Wang; Li-Li Zhang; Ning An; Fei Yang (Environmental Science and Pollution Research, 2020)

Differential anthocyanin accumulation in radish taproot: importance of RsMYB1 gene structure - Biao Lai; Yuanyi Cheng; Hong Liu; Qiuxia Wang; Qi Wang; Chunlan Wang; Rui Su; Fabo Chen; Huicong Wang; Lina Du (Plant Cell Reports, 2020)

Mercury exposure in sedentary and migratory Charadrius plovers distributed widely across China - Tongping Su; Xin Lin; Qin Huang; Demeng Jiang; Chi Zhang; Xuecong Zhang; Caroline Dingle; Eben Goodale; Pinjia Que; Rui Wang; Yang Liu (Environmental Science and Pollution Research, 2020)